Analysis of chromosomal aberrations in workers exposed to low level benzene. Issue 1 (January 1990) - Yardley-Jones, A; Anderson, D; Lovell, D P; Jenkinson, P C
Abstract : Metaphase chromosome preparations were analysed as part of a larger study from a population occupationally exposed to benzene and compared with a control group. Forty eight of the 66 exposed individuals and 29 of the 33 controls had samples in which metaphase spreads could be evaluated. The incidence of chromosomal aberrations (particularly chromatid deletions and gaps) in the exposed group were slightly increased compared with the control group. This increase was of borderline significance in parametric statistical tests but was significant using Fisher's exact test. No lifestyle factors had any consistent effect on the incidence of chromosome aberrations, although there was a small reduction in gaps with increasing cigarette smoking. Older individuals had a higher incidence of chromosome exchanges and "other" aberrations. Individuals who reported a recent viral illness had a higher incidence of aberrations particularly gaps. There was no evidence of any correlation in the incidence of chromosome aberrations with any of the other biological parameters previously reported. The increased incidence of aberrations seen in the group exposed to benzene may result from a history of exposure to benzene. Nevertheless, other explanations such as sampling, interindividual variability, and unintentional bias in the selection of two groups cannot be excluded.